amj 2019
DOI: 10.35841/1836-1935.12.12.337-343
|View full text |Cite
|
Sign up to set email alerts
|

Multiple sclerosis following bariatric surgery: A report of five cases

Abstract: Multiple sclerosis (MS) is a debilitating chronic inflammatory demyelinating disease that affects the central nervous system. The underlying cause of multiple sclerosis is unknown, yet there are various predisposing factors. Currently, bariatric surgery is an increasingly common solution for obesity. It has been reported that bariatric procedures result in miscellaneous neurological complications. To the best of our knowledge, this is the first case series to report the occurrence of MS following bariatric sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Obesity induces a state of chronic, low-grade inflammation that arises from the production of inflammatory mediators driven by adipose tissue macrophages. 16 The chronic inflammatory state may contribute to explain why obesity has been associated with increased disability and progression of MS. 3,2 However, several reports have associated metabolic surgery with neurological symptoms occurring after the procedure, and case series have reported the occurrence of MS following both metabolic surgery 17 and after significant intentional weight loss. 18 It has been speculated that the subclinical inflammation might be exacerbated following metabolic procedures due to accelerated adipose tissue breakdown by lipolysis.…”
Section: Discussionmentioning
confidence: 99%
“…Obesity induces a state of chronic, low-grade inflammation that arises from the production of inflammatory mediators driven by adipose tissue macrophages. 16 The chronic inflammatory state may contribute to explain why obesity has been associated with increased disability and progression of MS. 3,2 However, several reports have associated metabolic surgery with neurological symptoms occurring after the procedure, and case series have reported the occurrence of MS following both metabolic surgery 17 and after significant intentional weight loss. 18 It has been speculated that the subclinical inflammation might be exacerbated following metabolic procedures due to accelerated adipose tissue breakdown by lipolysis.…”
Section: Discussionmentioning
confidence: 99%
“…Dr. Moghadasi et al reported four cases of definite MS after severe weight loss following nonsurgical dietary treatment. [ 23 ] Similarly, Foziah Alshamrani et al [ 24 ] reported five cases with new-onset MS following bariatric surgery, but no direct link was found between their surgery and occurrence of MS. Nonetheless, it is likely that nutritional deficiency, especially vitamin D deficiency, which is a known risk factor for MS, played a role in this issue.…”
Section: Ontextmentioning
confidence: 99%